2022
DOI: 10.3390/ph15101274
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Therapeutic Role of Metformin in Diabetic and Non-Diabetic Bone Impairment

Abstract: Metformin is a widely-used anti-diabetic drug in patients with type 2 diabetic mellitus (T2DM) due to its safety and efficacy in clinical. The classic effect of metformin on lowering blood glucose levels is to inhibit liver gluconeogenesis that reduces glucose production as well as increases peripheral glucose utilization. However, the factors such as hyperglycemia, insulin deficiency, reduced serum levels of insulin-like growth factor-1 (IGF-1) and osteocalcin, accumulation of advanced glycation end products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 122 publications
1
5
0
Order By: Relevance
“…Other investigators also found no differences in BMD and/or BMC in the whole skeleton, tibiae and femurs of rodents with experimental MetS [13,44]. In the same line, several researchers have been unable to demonstrate changes induced by fructose-rich or high fat/high fructose (HF/HF) diets in dynamic (MS/BS, MAR, BFR, cortical bone area, and cortical thickness) and/or static (BV/TV Tb.N, Tb.Sp, Tb.Th, Ob.S/BS, Oc.S/BS) histomorphometric parameters [13,15,43],…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other investigators also found no differences in BMD and/or BMC in the whole skeleton, tibiae and femurs of rodents with experimental MetS [13,44]. In the same line, several researchers have been unable to demonstrate changes induced by fructose-rich or high fat/high fructose (HF/HF) diets in dynamic (MS/BS, MAR, BFR, cortical bone area, and cortical thickness) and/or static (BV/TV Tb.N, Tb.Sp, Tb.Th, Ob.S/BS, Oc.S/BS) histomorphometric parameters [13,15,43],…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators also found no differences in BMD and/or BMC in the whole skeleton, tibiae, and femurs of rodents with experimental MetS 13 44 . In the same line, several researchers have been unable to demonstrate changes induced by fructose-rich or high fat/high fructose (HF/HF) diets in dynamic (MS/BS, MAR, BFR, cortical bone area, and cortical thickness) and/or static (BV/TV Tb.N, Tb.Sp, Tb.Th, Ob.S/BS, Oc.S/BS) histomorphometric parameters 13 15 43 , or in bone biomechanical properties 44 . Thus, given our present results and those of other investigators, it is suggested that rodent models of fructose-induced MetS are not associated with significant alterations of bone tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It affects several aging-related processes, including bone deterioration, by suppressing cellular senescence and chronic inflammation and promoting autophagy ( 27 , 28 ). Previous studies demonstrated that metformin directly promoted osteoblastic differentiation of different kinds of stem cells (including umbilical cord mesenchymal stem cells ( 29 ), adipose-derived stem cells ( 30 ), dental pulp stem cells ( 31 ), and bone marrow derived mesenchymal stem cells ( 32 ), enhanced the anabolic action of the bone (including beneficial effects on bone microarchitecture, bone mineral density, and bone turnover markers), and improved bone quality in patients with T2DM ( 33 36 ). Furthermore, a previous report suggested a potential benefit of metformin in contributing to decreased bone cancer risk in T2DM patients ( 37 ).…”
Section: Introductionmentioning
confidence: 99%